Intramuscular Fentanyl and Ketorolac Associated with Superior Pain Control After Pediatric Bilateral Myringotomy and Tube Placement Surgery: A Retrospective Cohort Study. (January 2017) - Stricker, Paul A.; Muhly, Wallis T.; Jantzen, Ellen C.; Li, Yue; Jawad, Abbas F.; Long, Alexander S.; Polansky, Marcia; Cook-Sather, Scott D.
Abstract : BACKGROUND: Bilateral myringotomy and pressure equalization tube insertion (BMT) is the most common surgery in children. Multiple anesthetic techniques for BMT have been proposed, but that which reliably promotes ideal recovery remains unclear. We sought to assess associations between anesthetic regimens that included single-agent (fentanyl or ketorolac) or dual-agent (fentanyl and ketorolac) analgesic therapy and the primary outcome of maximal postanesthesia care unit (PACU) pain score. Secondary outcomes included in-hospital rescue analgesic administration, recovery time, and emesis incidence. METHODS: Principal analysis was conducted on a retrospective cohort of 3669 children aged 6 months to <7 years who underwent BMT over a 16-month period and received intraoperative fentanyl and/or ketorolac. Routine anesthetic care included preoperative oral midazolam, general anesthesia via a mask maintained with sevoflurane and N2 O or air in O2, and intramuscular analgesic administration. Multivariable analyses were performed examining relationships between analgesic regimen with the following outcomes: maximum PACU Face, Legs, Activity, Cry, and Consolability (FLACC) score = 0 or 7 to 10, oxycodone administration, and time to discharge readiness. Demographic variables, midazolam exposure, and location (main hospital vs ambulatory surgery center) were included in the multivariable analyses as potential confounders. Associations with postoperative vomiting were studied separately in 2725 children from a subsequent, nonoverlapping 12-month period using similar inclusion criteria. Fentanyl and ketorolac dose–response relationships were evaluated for selected outcome variables. RESULTS: Maximum FLACC = 0, maximum FLACC score of 7 to 10, and oxycodone rescue were most strongly associated with dual-agent therapy versus single-agent ketorolac: odds ratios 4.89 (95% confidence interval [CI], 4.04–5.93), 0.13 (95% CI, 0.10–0.16), and 0.11 (98.3% CI, 0.09–0.14), respectively, P < .001 for each). Minor associations were found for age, Hispanic ethnicity, midazolam, and location, and none for sex or race. For subjects managed with higher dose fentanyl (≥1.5 µg/kg) and ketorolac (≥0.75 mg/kg), 90% had no demonstrable pain, agitation, or distress. Mean discharge readiness times were 21 ± 11 minutes (ketorolac), 26 ± 16 minutes (fentanyl), and 24 ± 14 minutes (dual) ( P < .0001). Postoperative emesis incidences associated with ketorolac (2.7%) versus dual therapy (4.5%) were not different ( P = .08). CONCLUSIONS: In this large retrospective pediatric BMT study, combination intramuscular fentanyl/ketorolac was strongly associated with superior PACU analgesia and reduced need for oxycodone rescue without clinically significant increases in recovery time or emesis incidence. Combination fentanyl at 1.5 to 2 µg/kg and 1 mg/kg ketorolac was associated with optimal outcomes. Dual therapy appears similarly effective in children of either European Caucasian or African ancestry or of Hispanic ethnicity.